(untitled) (Comparative Professional Pedagogy, 2022)
The article considers and analyzes a new generation of students who have specific abilities and skills to work with modern digital devices. The term «digital natives», determined by the American researcher M. Prensky, has its synonyms – generation Z or network generation. Each generation is distinguished by certain values inherent in its representatives, has its own objectively determined, spontaneously formed social program, which depicts the state of material and spiritual culture, type of social relations, specific material and ideal relations through which the generation is formed. Generation Z also has its values and features. The aim of the study is to analyze the views of foreign researchers on the main characteristics and stereotypes of Generation Z as a new generation of students of higher education. Therefore, it is not surprising that many scientists, both practitioners and theorists (including psychologists, educators, and methodologists) pay close attention to the development of digital technologies and their impact on worldviews, relationships with other people, life in general. A number of characteristic features of Generation Z has been highlighted and characterized: freedom, personalization, information control, honesty, cooperation, entertainment and satisfaction, speed, desire for innovation. Two approaches to assessing the capabilities of modern students – Generation Z have been presented, and both positive and negative stereotypes of the generation (distraction syndrome, Internet addiction, health problems, social immaturity, low motivation, selfishness, narcissism, etc.) have been analyzed. Each subsequent generation (generation Z, Alpha) will always be different from the previous generation, because there are many different factors (external or internal) that affect the formation of the generation. The task of modern education is to study and analyze the changes taking place in ICT, the educational process, society and to predict the impact of these changes on the educational process and on students.